Calculus early transcendentals - Stewart, James (Brooks/Cole Cengage Learning, 2012)
This text embodies the broad principles of calculus reform - conceptual understanding motivated by real-world applications and the application of the rule of four in numerical, visual, algebraic and verbal interpretations.